Impact of smartphone use on quality of sleep among medical students - Kurugodiyavar, Mahesh D.; H. R., Sushma; Godbole, Maneesha; Nekar, Manjunath S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Smartphone with its various functionalities has become an essential part of our daily activities and its use has been increasing. This has raised concern about its overuse and addiction especially in students. It is known that poor sleep is very common among medical students; there are many studies on sleep quality and its determinants in medical students but very few relating sleep quality and smartphone addiction. The main objective of this study was to investigate the relationship between smartphone use severity and sleep quality among medical students of KIMS, Hubballi. Methods: A cross‑sectional study on sample of 240 undergraduate medical students KIMS, Hubballi was conducted. Students were assessed using a self-administered questionnaire, Smart phone addiction scale (SAS) and Pittsburgh sleep quality inventory (PSQI). SAS score and PSQI scores were co-related. Hierarchical regression analyses were conducted to identify the variables independently associated with level of sleep quality. Results: Out of 240 subjects 117 (48.75%) were poor sleepers & 123 (51.25%) were good sleepers according to PSQI global sleep score. According to SAS score 123 (51.2%) were low users and 117 (48.75%) were high users of Smart phone. The mean (SD) PSQI global score was 4.8 (2.49) and mean (SD) SAS score was 102.93 (22.13). There was positive correlation between SAS score & PSQI score (r=0.343, p<0.001). Gender (β=0.141, p=0.021) & SAS score (β=0.292, p<0.001) were the significant predictors of global PSQI score. Conclusions: This study concludes that in medical students smartphone addiction affects sleep quality significantly and males are particularly more at risk of having poor sleep quality due to excessive smartphone use.